"People don't understand what goes on in here": A consensual qualitative research analysis of inmate-caregiver perspectives on prison-based end-of-life care. (May 2018) - Depner, Rachel M; Grant, Pei C; Byrwa, David J; Breier, Jennifer M; Lodi-Smith, Jennifer; Luczkiewicz, Debra L; Kerr, Christopher W
Background: The age demographic of the incarcerated is quickly shifting from young to old. Correctional facilities are responsible for navigating inmate access to healthcare; currently, there is no standardization for access to end-of-life care. There is growing research support for prison-based end-of-life care programs that incorporate inmate peer caregivers as a way to meet the needs of the elderly and dying who are incarcerated. Aim: This project aims to (a) describe a prison-based end-of-life program utilizing inmate peer caregivers, (b) identify inmate-caregiver motivations for participation, and (c) analyze the role of building trust and meaningful relationships within the correctional end-of-life care setting. Design: A total of 22 semi-structured interviews were conducted with inmate-caregivers. Data were analyzed using Consensual Qualitative Research methodology. Setting/participants: All inmate-caregivers currently participating in the end-of-life peer care program at Briarcliff Correctional Facility were given the opportunity to participate. All participants were male, over the age of 18, and also incarcerated at Briarcliff Correctional Facility, a maximum security, state-level correctional facility. Results: In total, five over-arching and distinct domains emerged; this manuscript focuses on the following three: (a) program description, (b) motivation, and (c) connections with others . Conclusion: Findings suggest that inmate-caregivers believe they provide a unique and necessary adaptation to prison-based end-of-life care resulting in multilevel benefits. These additional perceived benefits go beyond a marginalized group gaining access to patient-centered end-of-life care and include potential inmate-caregiver rehabilitation, correctional medical staff feeling supported, and correctional facilities meeting end-of-life care mandates. Additional research is imperative to work toward greater standardization of and access to end-of-life care for the incarcerated.